Pharmacopoeial Requirements for Elemental Impurities in Radiopharmaceuticals (Review) - V. M. Shchukin; N. E. Kuz'mina; R. D. Ruziev; D. A. Pripadchev; M. A. Kuznetsov (Регуляторные исследования и экспертиза лекарственных средств, 2023)
INTRODUCTION. Current risk-based general strategies for the control of elemental impurities in medicinal products, as documented in the elemental impurity monographs of national and world pharmacopoeias, do not apply to radiopharmaceuticals. Manufacturers of radiopharmaceuticals have to determine and substantiate the lists of specified elemental impurities and their limits.AIM. This study aimed to develop a control strategy for elemental impurities in radiopharmaceuticals by analysing the requirements of national and world pharmacopoeias to the levels of specified elemental impurities in radiopharmaceuticals.DISCUSSION. Limits for the amounts of elemental impurities in specific radiopharmaceuticals are provided in individual monographs of pharmacopoeias (24 monographs in the European Pharmacopoeia, 7 monographs in the Indian Pharmacopoeia, 7 monographs in the State Pharmacopoeia of the Russian Federation, 6 monographs in the United States Pharmacopeia, 6 monographs in the Japanese Pharmacopoeia, 6 monographs in the Pharmacopoeia of the People’s Republic of China, and 4 monographs in the Korean Pharmacopoeia). Individual monographs for the same radiopharmaceuticals differ in the lists of elemental impurities and the corresponding limits. Moreover, these monographs lack common criteria for selecting elemental impurities and establishing limits for them. In most cases, limits are set for the parent non-radioactive elements, the elements that are added as components of radiolytic stabilisers or sorbents (Ti, Zr, Sn, and Al oxides), and the elements that decrease radiolabelling efficiency (Cu, Fe, Pb, and Zn in 177Lu solutions; Cu, Cd, and Fe in 111InCl solutions; Cd, Cu, Fe, Pb, and Zn in 90Y solutions; etc.). Elemental impurity limits for radiopharmaceuticals are calculated on the basis of the acceptable impact on the physicochemical, biological, and radiochemical properties of the product used and the dose administered. The elements that lack specified permitted daily exposure (PDE) limits are subject to specification if these elements affect the target organ or the process of medicinal product radiolabelling. There is also no unified approach to limiting the amounts of elemental impurities in radiopharmaceutical precursors.CONCLUSIONS. This article provides radiopharmaceutical manufacturers with a control strategy for elemental impurities in finished medicinal products, based on assessing the risk of elemental impurities having a negative impact on the quality attributes of medicinal products. This strategy includes generalised criteria for selecting the list of specified impurities and their limits for radiopharmaceuticals, which significantly streamlines the preparation of regulatory documentation concerning this quality attribute.